Non-Suicidal Self-Injury Among Incarcerated Adolescents: Prevalence, Personality, and Psychiatric Comorbidity - Koposov, Roman; Stickley, Andrew; Ruchkin, Vladislav (Frontiers in Psychiatry, 2021)
Introduction: Non-suicidal self-injury (NSSI) is common among adolescents and is often associated with psychiatric comorbidity and suicide. Incarcerated adolescents represent a risk group for NSSI, but research on this population has been limited and no studies have been conducted in Russia. To address this deficit, this study examined NSSI and the factors associated with it among youth in a juvenile correctional facility in Russia. Methods: NSSI and psychopathology were assessed using a semi-structured psychiatric interview and self-report questionnaire in 368 incarcerated male juvenile delinquents aged 14-19 years (mean age 16.4 years, S.D. 0.9) from Northern Russia. Chi-square tests and t-tests were used to compare groups. Results: 18.2% (n=67) of the study participants described a previous history of NSSI. The NSSI group had higher rates of anxiety disorder, post-traumatic stress disorder (PTSD), depression, community violence exposure and scored higher on most of the Youth Self-Report problem scales. In addition, 38.6% of the NSSI group reported frequent suicidal ideation and had thought about a specific suicide method, as compared to 17.4% in the No-NSSI group. Delinquents with NSSI also differed significantly from the No-NSSI group on self-directedness (lower) and self-transcendence (higher) personality traits. Conclusion: NSSI is common in incarcerated juvenile delinquents in Russia and is associated with extensive psychiatric comorbidity and suicidal ideation. NSSI is also associated with specific personality traits. Our results suggest a need for early diagnosis and treatment of NSSI in delinquent youths.